Efficiently functionalized oxacalix[4]arenes: Synthesis, characterization and exploration of their biological profile as novel HDAC inhibitors. Issue 3 (1st February 2016) - Mehta, Viren; Athar, Mohd; Jha, P.C.; Panchal, Manthan; Modi, Krunal; Jain, V.K.
Graphical abstract: Abstract: A series of novel substituted oxacalix[4]arene has been synthesized and explored for their biological profile by evaluating anticancer, antifungal and antibacterial properties. The derivatives have been characterized by various spectroscopic techniques such as IR, 1 H NMR, 13 C NMR and Mass spectrometry. Many compounds showed strong inhibition (MIC) in the range of ∼0–50 μM with interesting cytotoxic activities against Hela cells in particular. The compounds were theoretically evaluated by docking studies as potential histone deacetylase inhibitors (HDACi). The study indicates that compounds bound adequately with HDAC, and hence complemented the experimental findings.